Quo vadis microcredit in Portugal? A case study of the day-to-day of an entrepreneur - Silva, J.; Esperança, J. P.; Almeida, I. D. (Ciem2018 – 8ª Conferencia Ibérica de Emprendimiento, 2018)
A literature survey shows conflicts among the expected advantages of microcredit public-policies that might lead to discomfort on decision-making, and self-protection reactions due to increasing social demand for accountability. So, decisionmakers lacking skills and sensitiveness to the entrepreneurial phenomenon, set assessment criteria, based on banking practice, inadequate to unemployed, young, low income entrepreneurs. Together with unorganized processes, this situation produces disrespectful loan proposals ignoring experts’ opinions and business plans/contexts. The exploratory case of a Mutual Guarantee Society guaranteed by public funding: exemplifies ridiculous loan proposals for microcredit funding, conflicting with social grounds; shows entrepreneurs difficulties in accessing microcredit public-policies.